Perancangan Indoor Shape-Changing Fashion Pop-Up Store dengan Sistem Knockdown - Suryawan, Vania Stella (Intra, 2015)
Nowadays, there are many new comers in fashion brand selling their products online. For more promotion need, they do the promotion by meeting their customers directly through a pop-up store. Pop-up store is a retail store that available in a short period of time. This design aims to put on trial of the knockdown system, the interior elements configuration, and the design of indoor shape-changing pop-up store as a promotion media of a brand. This design refers to fashion such as clothing, bags, and shoes. This design uses design thinking method by David Kelley which consists of empathize, define, ideate, prototype, test, and iterate. The result shows that the knockdown uses bolt and screw system, and the pop-up store design uses modular system. By using the knockdown system, the pop-up store can be overhauled easily and fast. Besides that, through the modular system, those modules can be used many times with different final looks of the pop-up store.